Mapping the dialogue: Decoding alveolar stem–niche interactions - Ahmad N. Nabhan; Anne Biton; Christine Everett; Conrad Foo; Diana Wu; Joshua D. Webster; Alina A. Alam; Elisa Penna; Sandra Rost; Neha Rohatgi; Rohit Reja; Ranel J. Tulpano; et al. (Proceedings of the National Academy of Sciences, 2026)
While cellular atlases have revealed remarkable phenotypic diversity, how cells navigate this landscape to influence tissue behavior remains poorly understood. We present an alveolosphere screening platform for investigating interactions between lung stem cells and their fibroblast niche. We assessed the role of 201 candidate genes in stem cells via imaging, then used chimeric RNAseq analysis for a transcriptome-wide understanding of cell-autonomous effects on stem cells and non-cell-autonomous effects on the niche. This phenome-transcriptome map uncovered cellular states and pathways regulating proliferation, metabolism, and immune signaling. Notably, stem cells influenced scar-forming and immune programs in fibroblasts. This injury response was dependent on stem cell identity; loss of Nkx2.1 , encoding the transcription factor conferring lung epithelial identity, rewired stem cell–niche interactions and had a greater non-cell-autonomous effect than eliminating the cancer genes Trp53, Egfr, or Cdkn2b . Our study highlights how functional atlases complement the cellular diversity revealed by descriptive methods.